Use of Cereal Waste in Increasing the Protein Content of Mixed Feed Products (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In the food sector, corn grain is used in the production of flour, cereal, pickles, sweets, corn oil, starch-molasses, beer, alcohol. Omixta is used as a raw material for the production of fodder products, and its grain is used as a nutritious feed for livestock. Corn seeds make up 9-10% of protein, 4-6% of fat, 65-70% of carbohydrates, and 14% of vitamins. Wheat bran, chaff, and straw are very rich in proteins and carbohydrates. Wheat grain consists of 73.6% carbohydrate, 10.8% protein, 2.2% fat, 1.8% ash, and 12% water. Moss is the most protein-rich raw material in the preparation of Omixta fodder products. Mosh seeds contain 24-28% protein, 46-50% carbohydrates, 2-4% fat, 8% lysine, 7% arginine.